Application of the obstacle element in the WAsP (Wind Atlas Analysis and Application Program) flow model - HRADIL, Miloslav (Contributions to Geophysics and Geodesy, 2021)
Apart from orography and surface roughness various obstacles affect the input meteorological data and may play an important role when modelling the wind speed and direction in a complex terrain. One of the tools enabling to describe and, as the case might be, eliminate the effect of the obstacles is the WAsP model, product of the Risoe National Laboratory in Denmark. The Czech Hydrometeorological Institute (CHMI) has used the WAsP model for a number of years to solve the meteorology issues of designing the of wind power plants; by way of an example of projects from the Protivanov locality (49° 28′ 38′′ N, 16° 49′ 54′′ E) in the Drahanská Uplands we show how the obstacles, namely buildings in the vicinity of the station, affect the quality of extrapolation of the parameters of wind speed and wind power density. Apart from standard measurements conducted at a CHMI permanent meteorological station at 10 m above the terrain, two special-purpose tower measurements have been conducted at 40 m and 55 m above the terrain for several years in this locality. These ambulant measurements enabled to verify the model calculations and methods. In this case for heights of 10–55 m above the terrain, relatively strongly influenced by obstacles, we saw a typical error of estimation of 15–20% in the mean wind speed; for the wind power density, and/or the expected annual production of energy the error of estimation may even be 50–80%.